Pengaruh Media Pembelajaran Quizlet Terhadap Hasil Belajar Siswa pada Mata Pelajaran Informatika di SMPN 4 Kuningan - Dwi Utami, Ovy; Mahpudin, Asep (Indo-MathEdu Intellectuals Journal, 2025)
The effect of Quizlet learning on student learning outcomes in Informatics subjects at SMPN 4 Kuningan. This research uses a quantitative research method. The research design used in this study is a quasi-experimental with a pretest-posttest control group design. The population in this study consists of all eighth-grade students at SMPN 4 Kuningan, totaling 350 students. The sampling technique used in this study is Cluster Sampling. The sample in this study consists of 70 students. The data analysis techniques in this study include normality test, homogeneity test, and hypothesis testing using the t-test. The research results show an increase in learning outcomes, with an average pretest score of 44.29 and a posttest score of 77.14. The hypothesis test results show that the t-value of 33.955 is greater than the table t-value of 1.690 and the significance value (2-tailed) of 0.000 < 0.050. Therefore, it can be concluded that there is a significant difference between the pretest and posttest results. Thus, the null hypothesis is rejected and the alternative hypothesis is accepted, meaning that the use of Quizlet is effective in improving students' learning outcomes